2X - 3 + 3X = 37
add the X terms together
5X - 3 = 37
add 3 to each side
5X = 40
divide both sides by 5
X = 8
check in original equation
2(8) - 3 + 3(8) = 37
16 - 3 + 24 = 37
13 + 24 = 37
37 = 37
checks
It can be simplified in the form of: 2x3+9x2-7x-34 = 0
x=5
4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.
Ten. That means 3x equals 30, and 30 divided by three is ten.
Substitute y = 3x + 1 into first equation: 3x + 1 + x = 37 ie 4x + 1 = 37 Subtract 1 from each side: 4x = 36 Divide each side by 4: x = 9 so y = 28
3x+7=37 -7 -7 3x=30 /3 /3 x=10
It can be simplified in the form of: 2x3+9x2-7x-34 = 0
2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7
4
x=5
4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.
3x + 4 = 37 Subtracting 4 from both sides 3x + 4 - 4 = 37 - 4 3x = 33 Dividing both sides by 3, we get x = 11
Ten. That means 3x equals 30, and 30 divided by three is ten.
It is an equation and the value of x is 12
-108
Substitute y = 3x + 1 into first equation: 3x + 1 + x = 37 ie 4x + 1 = 37 Subtract 1 from each side: 4x = 36 Divide each side by 4: x = 9 so y = 28
no